Enabling a Smooth Transition: Responsible Chemistry Competencies for the European Green Deal - Jan Mehlich (CHIMIA)
Chemists are a vital part of the research and innovation (R&I) landscape. With their expertise, they shape progress and, thus, society. In order to live up to this responsibility, it is suggested to prepare young chemists for their future role as innovators with proper training. Here, it is important to go beyond the good scientific practice dimension of research integrity and add discourse performance and value assessments to the class outline of a “responsible chemistry” course. This becomes especially relevant in view of changing demands on chemical research and innovation as envisioned by the European Green Deal through its Horizon Europe funding scheme. This paper outlines the necessity of preparing chemists for the requirements of a green transition R&I policy and shows what that would mean for “ethics in chemistry” education.